The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.scitotenv.2019.03.439
|View full text |Cite
|
Sign up to set email alerts
|

Environmental sustainability of phosphorus recycling from wastewater, manure and solid wastes

Abstract: Phosphorus (P) is an important critical material essential for crops cultivation and animal husbandry. Effective phosphorous recycling is considered one of the most significant factors in alleviating its criticality. However, despite the importance of phosphorous recycling, its sustainability is not studied extensively. This paper aims to answer the question if recycling of phosphorus is an environmentally sustainable option. To address this problem, two issues are analyzed in this paper: energy consumption an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 83 publications
1
15
0
Order By: Relevance
“…Their results indicated that sludge-based phosphate fertilizers appeared to have higher environmental impacts than mineral phosphate fertilizers production, mainly due to their consumption of large amounts of electricity and reactants needed to recover phosphorus, and their low phosphorus content in comparison with phosphate rocks. Qualitatively similar conclusions were reported by Golroudbary et al (2019). On the contrary, Tonini et al (2019) suggested that the environmental impacts of recovering sewage derived P may be up to 81% less than mining P containing rock.…”
Section: Phosphorus Recovery Technologies At Wwtpsupporting
confidence: 77%
“…Their results indicated that sludge-based phosphate fertilizers appeared to have higher environmental impacts than mineral phosphate fertilizers production, mainly due to their consumption of large amounts of electricity and reactants needed to recover phosphorus, and their low phosphorus content in comparison with phosphate rocks. Qualitatively similar conclusions were reported by Golroudbary et al (2019). On the contrary, Tonini et al (2019) suggested that the environmental impacts of recovering sewage derived P may be up to 81% less than mining P containing rock.…”
Section: Phosphorus Recovery Technologies At Wwtpsupporting
confidence: 77%
“…In line with the concept of circular economy, we consider the estimated value of phosphorus recycling will increase by up to 50 % in the next 12-15 years (Golroudbary et al, 2019;Scholz and Wellmer, 2018). Moreover, we assume that there is no difference for a decision maker to choose primary or secondary sources.…”
Section: Tablementioning
confidence: 99%
“…The management policy of phosphorus supply chain in Europe is based on national policies of the Member States which differ with respect to economic benefits and environmental impact as well as resource scarcity and the advancement in the implementation of circular economy model (Stahel, 2016). In addition, the motivation for sustainable use of phosphorus in Europe is driven by the aspiration to implement the principles of circular economy (Golroudbary et al, 2019;Nesme and Withers, 2016). Therefore, recycling or recovery of phosphorus from waste streams has been proposed as a possible approach to managing its sustainable use.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, non-renewable resources like phosphate rocks, which are used in the industry of P fertilizers, are expected to become scarce in the future (Gasparatos et al 2019;Li and Marschner 2019). Furthermore, the mining processes disturb the environment (Golroudbary et al 2019;Grigatti et al 2015).…”
Section: Introductionmentioning
confidence: 99%